Evaluasi kualitas layanan menggunakan metode LibQUAL+^TM pada Amikom Resource Centre Universitas Amikom Yogyakarta - Dwiyantoro Dwiyantoro (Al-Kuttab : Jurnal Kajian Perpustakaan, Informasi dan Kearsipan, 2019)
Service is an important component in a library, good service will make the library can increase the level of user visits, so it is necessary to see the quality of services in the library, this is of course users who can provide an assessment of the quality in the library. Amikom Resource Center is one of the libraries that provide services to the academic community in the Amikom University in fulfilling information needs. Therefore, researchers are interested in evaluating the quality of services that exist in the Yogyakarta resource center amikom using the libqual method, in this study to see the quality of services available at Amikom Resorce Center. In this study the method used is descriptive quantitative, with data collection using questionnaires and observations, sampels in this study that amounted to 79 respondents. The results of this study, which is based on the calculation of service quality using the libqual method, found that the greatest AG gap is found in the Service of Affect dimension, which is 0.56 and the greatest SG gap is in the same dimension, Service of Affect with a value of 0.92. that the ability and attitude of librarians in serving is greater than the reality received so far, and the overall value of the dimensions of Adequacy Gap (AG) positively is 1.05, indicating that the services provided by Amikom Resousce Center have exceeded the minimum expectations of visitors. while for the total value of Superiority Gap (SG) is positive, which is 1.71, this indicates that the services provided have exceeded the ideal expectations of the users, so the users are "very satisfied" with the services they receive.